Criteria for Central Bank independence and inflation - Mukhamediyev, B.; Khitakhunov, A.; Temerbulatova, Zh.; Turarov, D. (Journal of Economic Research & Business Administration, 2022)
There are many studies on the relationship between central bank independence and inflation. A number of authors have come to the conclusion that there is a negative relationship between them, in which the independence of the central bank helps to reduce inflation. But other authors have questioned this conclusion. This study tested the hypothesis that there is a negative statistical relationship between the inflation rate and the values of the CWN and GMT indices of central bank independence, as well as their constituent sub-indices for developed and post-Soviet countries for 2001-2020. The methods of econometric and correlation analysis have established the absence of a statistically significant negative impact of the independence of central banks, measured by the CWN and GMT indices and their subindices, on inflation in developed and post-Soviet countries, which is true throughout the entire time interval. Graphical analysis and then econometric analysis showed no negative relationship between these indices, as well as their sub-indices, and inflation in certain years, both in developed and post- Soviet countries. Moreover, in some cases, on the contrary, their positive relationships were revealed. At the same time, based on quantitative estimates, it was concluded that the relationship between central bank independence and inflation weakens as it decreases. It requires verification and confirmation in the course of further research. Key words: central bank independence, inflation, CWN and GMT indices, developed countries, post-Soviet countries.